2015
DOI: 10.24959/ophcj.15.850
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and analgesic properties of N-(benzyl)-2-hydroxy-9-methyl-4-oxo-4H-pyrido[1,2-a]pyrimidine-3-carboxamides

Abstract: -hydroxyquinolin-2-one and 2-hydroxy-9-methyl-4-oxo-4Н-pyrido[1,2-a]pyrimidine nuclei has been made. СИНТЕЗ ТА АНАЛГЕТИЧНІ ВЛАСТИВОСТІ N-(БЕНЗИЛ)-2-ГІДРОКСИ-9-МЕТИЛ-4-ОКСО-4Н-ПІРИДО[1,2-a] В той же час сигнали ароматичних протонів бензиламідних фрагментів на-впаки в усіх випадках зміщені у відносно сильне поле та зосереджені на дуже вузьких відрізках спектрів, за ра-хунок чого піддаються досить сильному спотворенню. За результатами первинного фармакологічного скри-нінгу встановлено, що на стандартній моделі оц… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Interestingly, the resonance signals of protons of H-7 and H-9 in all N-(benzyl)-2-hydroxy-8-methyl-4-oxo-4H-pyrido[1,2-a]pyrimidine-3-carboxamides (5a-n) change places compared to those in the 1 H NMR spectrum of the starting ester (4) [20]. It is ratter difficult to give an unambiguous explanation for this fact without more research since this effect was not observed in 9-methyl substituted isomers previously studied [19]. The signals of aromatic protons of arylalkylamide fragments, as a rule, are markedly shifted upfield and focused…”
Section: метилювання положення 8 піридинової частини молекули N-(бензmentioning
confidence: 61%
See 1 more Smart Citation
“…Interestingly, the resonance signals of protons of H-7 and H-9 in all N-(benzyl)-2-hydroxy-8-methyl-4-oxo-4H-pyrido[1,2-a]pyrimidine-3-carboxamides (5a-n) change places compared to those in the 1 H NMR spectrum of the starting ester (4) [20]. It is ratter difficult to give an unambiguous explanation for this fact without more research since this effect was not observed in 9-methyl substituted isomers previously studied [19]. The signals of aromatic protons of arylalkylamide fragments, as a rule, are markedly shifted upfield and focused…”
Section: метилювання положення 8 піридинової частини молекули N-(бензmentioning
confidence: 61%
“…Taking into account these data and continuing our extensive research in searching new promising analgesics among amide derivatives of 4-hydroxy-2-oxo-1,2-dihydroquinoline-3-carboxylic acids [16] and structurally-related heterocyclic systems [17,18] [19] were the theoretical background to involvement of these compounds to the range of the objects studied. A detailed analysis of the structure of these substances indicates that the attempt can be made to intensify their biological effect by the chemical modification of the pyridine moiety of the molecule bicyclic base, namely by displacement of the methyl group to another position, for example position 8.…”
Section: метилювання положення 8 піридинової частини молекули N-(бензmentioning
confidence: 99%